Makna Teologi Gamelan Gambang dalam Upacara Ngaben - Ni Wayan Suantini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The Gamelan Gambang is one of the ancient gamelans found in the archipelago. This can be seen from the material which is made of wood and the blades are made of bamboo. The Gamelan Gambang is a gamelan that functions as a guardian in the Ngaben ceremony in Bali. This gamelan is thought to have developed around the XIII and XV centuries. Playing the Gamelan Gambang in the Ngaben ceremony is a form of service to God Almighty. The rhythm of the Gamelan Gambang is such an expression of human gratitude and desire to be close to God. Efforts to unify refinement, concentration and movement when playing the gamelan can provide its own experience, and is able to place human thought waves on theta waves. When the gamelan is played in a ceremony, it means reciting Sang Hyang Dasa Aksara. Sang Hyang Dasa Akasara is a medium for worshiping the Dewata Nawa Sanga and is the prabawa of Ida Sang Hyang Widhi Wasa. Thus it can be seen that the Gamelan Gambang is a sacred art that has the sound of the Genta Pinara Pitu.